Rotavirus specific maternal antibodies and immune response to RV3-BB neonatal rotavirus vaccine in New Zealand. Issue 5 (4th May 2017) - Chen, Mee-Yew; Kirkwood, Carl D.; Bines, Julie; Cowley, Daniel; Pavlic, Daniel; Lee, Katherine J.; Orsini, Francesca; Watts, Emma; Barnes, Graeme; Danchin, Margaret
ABSTRACT: Background: Maternal antibodies, acquired passively via placenta and/or breast milk, may contribute to the reduced efficacy of oral rotavirus vaccines observed in children in developing countries. This study aimed to investigate the effect of rotavirus specific maternal antibodies on the serum IgA response or stool excretion of vaccine virus after any dose of an oral rotavirus vaccine, RV3-BB, in parallel to a Phase IIa clinical trial conducted at Dunedin Hospital, New Zealand. At the time of the study rotavirus vaccines had not been introduced in New Zealand and the burden of rotavirus disease was evident. Methods: Rotavirus specific IgG and serum neutralizing antibody (SNA) levels in cord blood and IgA levels in colostrum and breast milk samples collected ∼4 weeks, ∼20 weeks and ∼28 weeks after birth were measured. Infants were randomized to receive the first dose of vaccine at 0–5 d (neonatal schedule) or 8 weeks (infant schedule). Breast feeding was with-held for 30 minutes before and after vaccine administration. The relationship between rotavirus specific IgG and SNA levels in cord blood and IgA in colostrum and breast milk at the time of first active dose of RV3-BB vaccine and level of IgA response and stool excretion after 3 doses of vaccine was assessed using linear and logistic regression. Results: Forty infants received 3 doses of RV3-BB rotavirus vaccine and were included in the analysis of the neonatal and infant groups. Rotavirus specific IgA in colostrum (neonatal schedule group) and breast milk at 4 weeks (infant schedule group) was identified in 14/21 (67%) and 14/17 (82%) of infants respectively. There was little evidence of an association between IgA in colostrum or breast milk IgA at 4 weeks, or between cord IgG or SNA level, and IgA response or stool excretion after 3 doses of RV3-BB, or after one dose (neonatal schedule) (all p>0.05). Conclusions: The level of IgA in colostrum or breast milk and level of placental IgG and SNA did not impact on the serum IgA response or stool excretion following 3 doses of RV3-BB Rotavirus Vaccine administered using either a neonatal or infant schedule in New Zealand infants.